Euphemism, the art of saying it politely : Northern Sotho novels in perspective - Maitja, Phuti Phineas (My University, 2013)
Refer to the document
Thesis (M.A. (African Languages)) -- University of Limpopo, 2013
Keywords: Euphemism; Northern Sotho language; Euphemism; African language -- Euphemism